Genetic influence on urinary vitamin D binding protein excretion and serum levels: a focus on rs4588 C>A polymorphism in the GC gene - Doğan, Durmus; Özcan, Eda Gül; Çakır, Dilek Ülker; Sılan, Fatma (Frontiers in Endocrinology, 2023)
Introduction: Vitamin D binding protein (VDBP) plays a crucial role in vitamin D transport and metabolism. The rs4588-A polymorphism of the GC gene, encoding VDBP, has been associated with altered serum VDBP and 25-hydroxyvitamin D (25OHD) levels. However, the mechanisms underlying these effects remain unclear. We aimed to investigate the relationship between urinary VDBP excretion and serum VDBP and 25OHD levels in individuals with and without the rs4588-A allele.A cross-sectional study was conducted on 109 children (mean age: 11.96 years) to explore the impact of rs4588-A on vitamin D metabolism and urinary VDBP excretion. Biochemical analyses determined serum 25OHD and VDBP levels, and urinary VDBP-to-creatinine ratio (u-VDBP/Cr). Genotyping for rs4588 SNP was performed using LightSNiP assay. Statistical analyses included correlation, linear regression, and comparison between allele groups.Results: Participants carrying the rs4588-A allele exhibited lower serum 25OHD levels compared to non-carriers (median (IQR): 11.85 (3.5) vs. 12.86 (4.9), p = 0.023). However, no statistically significant differences were observed in serum VDBP levels (126.34 ± 59.3 in rs4588-A vs. 136.49 ± 51.3 in non-rs4588-A, p = 0.141) or in u-VDBP/Cr (median (IQR): 0.4 (0.35) in rs4588-A vs. 0.386 (0.43) in non-rs4588-A, p = 0.189) between the two allele groups (Figure 2). A significant inverse correlation between u-VDBP/Cr and serum VDBP levels was found only in rs4588-A carriers (r = -0.367, p = 0.024). No such correlation was observed in non-carriers or the entire cohort. A linear regression analysis confirmed the impact of u-VDBP/Cr on serum VDBP levels in rs4588-A carriers